Stark sublevels in Tm3+–Yb3+ codoped Na2Y2B2O7 nanophosphor for multifunctional applications. Issue 44 (16th May 2015) - Soni, Abhishek Kumar; Dey, Riya; Rai, Vineet Kumar
<x xml:space="preserve">Abstract</x> The phase and crystal structure of the Na2Y2B2O7:Tm3+–Yb3+ inorganic phosphor prepared by solution combustion method have been identified. These observations show that the developed material can be used in optical devices and for biological applications.